A Comparative Study Between Two Different Doses of Dexmedetomidine Combined with Ropivacaine in Ultrasound Guided Supraclavicular Brachial Plexus Block - Singh, Jeevan; Shakya, Samir; Ghimire, Anuranjan; Saha, Sanjay; Singh, Parikshit Bikram (Journal of College of Medical Sciences-Nepal, 2018)
Background: Though, various studies have been conducted to show the efficacy of dexmedetomidine as an adjuvant to brachial plexus block, there is no clear consensus for its optimal dose. We compared 2 different doses of dexmedetomidine (1mcg/kg Vs 2mcg/kg) with ropivaciane in USG guided brachial plexus block for the quality of anesthesia and analgesia. Materials and Methods: Fifty patients (18-50years, 50-60kgs), ASA PS I and II undergoing surgery of upper limb were enrolled in this prospective, double blind, randomized control trial. Group Rd received 19ml of 0.5% Ropivaciane with 1mcg/kg of dexmedetomidine (total 20ml), and Group RD received 19ml of 0.5% Ropivacaine with 2mcg/kg of dexmedetomidine (total 20ml). Onset and duration of sensory and motor block, duration of analgesia, sedation score, hemodyanamic changes were compared. We also monitored for various un towards effects. Results: The onset time of sensory and motor block (9.36±1.114 mins and 14.40 ± 1.528 mins in group Rd vs 8.32 ±0.945 mins and 12.40 ± 1.21 mins in group RD) were not significantly different between two groups (p-value > 0.05).The duration of sensory and motor block (596.20 ± 76.859 mins and 541.20±81.564 mins in group Rd vs 730.80 + 65.187 mins and 659.80±93.607 mins in group RD) were not significantly longer in group RD than group Rd (p-value > 0.05). The duration of analgesia (626.00±70.475 mins in group Rd vs 754.00±60.139 mins in group RD) were not significantly longer in group RD than group Rd (p-value > 0.05). Hemodynamic parameters were also comparable between two groups (p-value >0.05) but 3 patients in RD group (2mcg/kg) developed bradycardia and required treatment with atropine whereas in Rd group (1mcg/kg) none developed bradycardia. Conclusions: There is no significant difference in the onset and duration of block between the two groups. However, higher dose of dexmedetomidine is associated bradycardia. Hence, in comparision with 2mcg/kg, 1mcg/kg of dexmedetomidine is better adjuvant to 0.5% ropivaciane in terms of safety and effectiveness. Keywords: dexmedetomidine; ropivacaine; supraclavicular brachial plexus block.